إختصاص السلطات الإدارية المستقلة بتوقيع العقوبات – دراسة مقارنة - رؤوف زنداوي (My University, 2025)
The jurisdiction of independent administrative authorities to impose sanctions represents an important tool for ensuring respect for the law and protecting the rights of individuals. However, achieving a balance between authority and judicial oversight is essential to ensuring justice and equality, developing the legal framework regulating the work of these authorities, and strengthening oversight mechanisms to ensure that they do not exceed the limits of their jurisdiction. ............................... إن اختصاص السلطات الإدارية المستقلة في توقيع العقوبات يمثل أداة مهمة لضمان احترام القانون وحماية حقوق الأفراد، ومع ذلك فإن تحقيق التوازن بين السلطة والرقابة القضائية يعد أمرا ضروريا لضمان العدالة والمساواة وتطوير الإطار القانوني المنظم لعمل هذه السلطات، وتعزيز آليات الرقابة لضمان عدم تجاوزها لحدود اختصاصها. ............................ La compétence des autorités administratives indépendantes pour imposer des sanctions représente un outil important pour assurer le respect de la loi et protéger les droits des individus. Toutefois, il est essentiel de parvenir à un équilibre entre l’autorité et le contrôle judiciaire pour garantir la justice et l’égalité, développer le cadre juridique régissant le travail de ces autorités et renforcer les mécanismes de contrôle afin de s’assurer qu’elles n’outrepassent pas les limites de leur juridiction.
Keywords: Keywords: independent administrative authorities; imposition of sanctions; oversight mechanisms.; الكلمات المفتاحية: السلطات الإدارية المستقلة، توقيع العقوبات، آليات الرقابة.; Mots-clés : autorités administratives indépendantes; imposition de sanctions; mécanismes de contrôle.